When Law Speaks, Economy Acts: A Normative Assessment of Trump's Import Tariffs and Indonesia's Halal Industry Strategy for Economic Resilience - Mansyuroh, Firqah Annajiyah; Abdillah, Muhammad Torieq (SIYAR Journal, 2026)
This study analyzes the impact of U.S. President Donald Trump’s unilateral import tariffs under Section 232 of the Trade Expansion Act of 1962, which disrupted the multilateral trading system and triggered global protectionism. Using a normative legal approach grounded in international trade law, it examines the implications of these tariffs for Indonesia’s economic resilience and highlights the halal industry as an adaptive strategy. Findings show that Trump’s tariffs violate WTO principles such as Most-Favoured-Nation and non-discrimination, weakening multilateral legitimacy. Yet, this disruption offers Indonesia a chance to strengthen its halal industry through market diversification, domestic value chains, and ethical competitiveness. The study concludes that the halal sector represents a lawful and sustainable pathway to economic resilience amid declining global multilateralism.